2000
DOI: 10.1089/10763270050044434
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Analytical Methods for Quantitation of Isolated Porcine Hepatocyte Yields

Abstract: As cell-based therapies receive approval for clinical evaluation and use, the development of reliable methods to quantify cell number and control the dose of therapy delivered is becoming increasingly important. An example is the determination of the number and volume of primary porcine hepatocytes used in an extracorporeal treatment for patients with liver disease. Conventional cell counting using optical microscopy was compared against two alternate methods to quantify isolated porcine hepatocytes: (1) autom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…As the outcome of Nagata's study was significantly better than ours, this suggests that rendering the recipient in hepatic failure may not be essential. Is compatibility between pig CD47 and primate SIRP‐α essential if phagocytosis of the hepatocytes is to be avoided? As porcine hepatocytes (20‐30 μm) and primate macrophages (20‐50 μm) are of similar size, we suggest that the hepatocytes are too large to be phagocytosed by the macrophages. However, fragile hepatocytes could fragment, possibly from direct activation of recipient macrophages resulting in injury to the hepatocytes, and then be phagocytosed.…”
Section: Discussionmentioning
confidence: 86%
“…As the outcome of Nagata's study was significantly better than ours, this suggests that rendering the recipient in hepatic failure may not be essential. Is compatibility between pig CD47 and primate SIRP‐α essential if phagocytosis of the hepatocytes is to be avoided? As porcine hepatocytes (20‐30 μm) and primate macrophages (20‐50 μm) are of similar size, we suggest that the hepatocytes are too large to be phagocytosed by the macrophages. However, fragile hepatocytes could fragment, possibly from direct activation of recipient macrophages resulting in injury to the hepatocytes, and then be phagocytosed.…”
Section: Discussionmentioning
confidence: 86%
“…The hepatocellularity number obtained for the horse is higher than other species. One possible explanation for this may be due to the diameter of horse hepatocytes (14.6±4.8 µm) being smaller than the diameter of hepatocytes from other species; 19.2±0.6 µm in rat, 18.4±0.8 µm in pigs, and between 20-30 µm in human (Engelmann et al 1981;Stegemann et al 2000;Boyer et al, 2017). On the other hand, the microsomal protein value obtained from the horse was similar to values obtained for dog and rat; however, it was higher than that obtained for human (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, Stegemann et al. () demonstrated with sufficient precision and accuracy that the average size of isolated porcine hepatocytes remained consistent among individuals. The number of animals in our study does not enable a reliable comparison between males and females; however, we speculate that sexual dimorphism may explain, at least in part, this variability.…”
Section: Discussionmentioning
confidence: 99%
“…5, healthy pigs of the same age and breed with a similar total liver volume of 813 AE 85 mL (mean AE SD, see Table S1), and identical diet and handling may have significant interindividual differences at the level of hepatocytes evaluated within their tissue context. However, Stegemann et al (2000) demonstrated with sufficient precision and accuracy that the average size of isolated porcine hepatocytes remained consistent among individuals. The number of animals in our study does not enable a reliable comparison between males and females; however, we speculate that sexual dimorphism may explain, at least in part, this variability.…”
Section: Size Density and Fraction Of Bnhep Exhibit Considerable Intmentioning
confidence: 98%
See 1 more Smart Citation